👉 Try now NerdPal! Our new math app on iOS and Android
  1. calculators
  2. Quotient Rule Of Differentiation

Quotient Rule of Differentiation Calculator

Get detailed solutions to your math problems with our Quotient Rule of Differentiation step-by-step calculator. Practice your math skills and learn step by step with our math solver. Check out all of our online calculators here.

Symbolic mode
Text mode
Go!
1
2
3
4
5
6
7
8
9
0
a
b
c
d
f
g
m
n
u
v
w
x
y
z
.
(◻)
+
-
×
◻/◻
/
÷
2

e
π
ln
log
log
lim
d/dx
Dx
|◻|
θ
=
>
<
>=
<=
sin
cos
tan
cot
sec
csc

asin
acos
atan
acot
asec
acsc

sinh
cosh
tanh
coth
sech
csch

asinh
acosh
atanh
acoth
asech
acsch

1

Ici, nous vous montrons un exemple résolu étape par étape de règle du quotient de la différentiation. Cette solution a été générée automatiquement par notre calculatrice intelligente :

$\frac{d}{dx}\left(\frac{x}{x^2+1}\right)$
2

Appliquer la formule : $\frac{d}{dx}\left(\frac{a}{b}\right)$$=\frac{\frac{d}{dx}\left(a\right)b-a\frac{d}{dx}\left(b\right)}{b^2}$, où $a=x$ et $b=x^2+1$

$\frac{\frac{d}{dx}\left(x\right)\left(x^2+1\right)-x\frac{d}{dx}\left(x^2+1\right)}{\left(x^2+1\right)^2}$
3

Appliquer la formule : $\frac{d}{dx}\left(x\right)$$=1$

$\frac{x^2+1-x\frac{d}{dx}\left(x^2+1\right)}{\left(x^2+1\right)^2}$

Appliquer la formule : $\frac{d}{dx}\left(c\right)$$=0$, où $c=1$

$\frac{x^2+1-x\frac{d}{dx}\left(x^2\right)}{\left(x^2+1\right)^2}$
4

La dérivée d'une somme de deux fonctions ou plus est la somme des dérivées de chaque fonction.

$\frac{x^2+1-x\frac{d}{dx}\left(x^2\right)}{\left(x^2+1\right)^2}$

Appliquer la formule : $\frac{d}{dx}\left(x^a\right)$$=ax^{\left(a-1\right)}$, où $a=2$

$-2x\cdot x^{\left(2-1\right)}$

Appliquer la formule : $a+b$$=a+b$, où $a=2$, $b=-1$ et $a+b=2-1$

$-2x\cdot x$
5

Appliquer la formule : $\frac{d}{dx}\left(x^a\right)$$=ax^{\left(a-1\right)}$, où $a=2$

$\frac{x^2+1- 2x\cdot x}{\left(x^2+1\right)^2}$
6

Appliquer la formule : $ab$$=ab$, où $ab=- 2x\cdot x$, $a=-1$ et $b=2$

$\frac{x^2+1-2x\cdot x}{\left(x^2+1\right)^2}$
7

Appliquer la formule : $x\cdot x$$=x^2$

$\frac{x^2+1-2x^2}{\left(x^2+1\right)^2}$

Final answer to the exercise

$\frac{x^2+1-2x^2}{\left(x^2+1\right)^2}$

Are you struggling with math?

Access detailed step by step solutions to thousands of problems, growing every day!